Examining the Role of Self-Regulated Learning and Self-Efficacy in Reducing English Language Anxiety - Maesaroh, Siti; Bernadeta, Anggis; Citra, Alina Ria (CV. Akademi Merdeka, 2025)
This study examines the interaction between self-efficacy, self-regulated learning, and English language anxiety among secondary school and university students in Cirebon, West Java. The urgency of this research lies in the high levels of English language anxiety, which negatively affect students’ learning performance. Using path analysis on data from 289 participants, the results show that self-regulated learning significantly mediates the relationship between self-efficacy and English language anxiety (indirect effect = 0.281, p < 0.05). The model accounts for 31.5% of the variance in English language anxiety (R² = 0.315). These findings highlight the crucial role of self-regulation and metacognitive strategies in reducing anxiety and enhancing learning effectiveness. This research supports the need for intervention programs that strengthen self-efficacy and self-regulated learning, particularly within the local educational and cultural context of Cirebon. Further studies are recommended to explore other contextual factors more deeply.